Reliability-Centered Maintenance (RCM) Application for 15-Ton Overhead Traveling Crane in Kuala Lumpur Additional Vehicle 27 (KLAV27) Project Facility at Hartasuma Sdn. Bhd. (HSB) - Ismail, Imran Hazim; Omran, Mustapha Kamil; Mohd Noordin, Mohd Noor Fathullah; Yaman, Muhammad Zulhilmy (Progress in Engineering Application and Technology, 2023)
The research proposes a Reliability-Centered Maintenance (RCM) strategy to minimize the risk of equipment failure and improve the safety of the 15-ton overhead traveling crane at the Kuala Lumpur Additional Vehicle 27 (KLAV27) project facility at Hartasuma Sdn. Bhd. (HSB). The RCM strategy was developed using Failure Modes and Effects Analysis (FMEA) to identify the potential failure modes of the crane and their consequences. The results of the FMEA were used to develop a maintenance plan that includes preventive maintenance tasks and procedures to prevent or mitigate the identified failures. The RCM strategy is expected to reduce the risk of equipment failure, improve the safety of the crane, and save costs. The findings of the research will be used to improve the maintenance of the overhead traveling crane at HSB.